Performance Analysis of Relative GPS Positioning as Function of Communication Latency - Carvalho, Gustavo S.; Silva, Felipe O. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
GNSS has become the main navigation system around the world, providing position accuracy up to 10 m. Due its low-cost and versatility, many segments have benefited from it, such as surveying & mapping, agriculture, aviation, marine, and recreation. Nevertheless, many other modern-day applications have arisen demanding navigation technologies able to provide submeter position accuracy, still at low-cost. Relative Global Navigation Satellite System (RGNSS) is a well-known technique used to correct common-mode errors present in GNSS observables. RGNSS is susceptible to two main degradation factors, namely, communication latency and baseline separation between two GNSS receivers. This paper investigates the sensitivity of position estimation accuracy as function of communication latency between stationary Global Positioning System (GPS) receivers. As main contribution, we show that it is possible to achieve 1 m horizontal accuracy at 68% of probability with latency up to 1500 s. Experimental data collected from the Brazilian Network for Continuous Monitoring of GNSS (RBMC) are used to validate the analysis.